Entropic control on the desorption of oil molecular droplets in water from kerogen surface - Zhang, Zelong; Stephens, Adrienne; Wang, Jianwei (Frontiers in Earth Science, 2024)
Understanding the thermodynamics of interfacial interactions between oil and kerogen is imperative for developing technologies aimed at improving hydrocarbon recovery in reservoirs, especially in unconventional shale, which retains abundant hydrocarbons in a non-porous medium. The temperature effect on the interactions of a light oil molecular cluster with kerogen was investigated using molecular dynamics simulation. Non-polar and polar light oil droplets were modeled with clusters of 30 octane molecules and 30 octanethiol molecules in water, respectively. Kerogen was modeled with a molecular fragment from a mature type II kerogen. The potential of mean force calculations was performed at constant volume and temperature via umbrella sampling at temperatures in 300–500 K range, comparable to the reservoir temperatures of common shale plays. The results show that the free energy of desorption of oil droplets scales linearly with temperature and has a strong negative temperature dependence, suggesting a significant entropic contribution to the free energy and underscoring the fundamental basis of the thermal stimulation technique for improved oil recovery. The simulations suggest that single molecules cannot represent the interactions of an oil droplet with the kerogen surface. The internal dynamics within the droplets play an important role in the strong temperature dependence of the free energy. The calculated free energy, contact angle, and surface tension of oil droplets are comparable with observations and provide an improved understanding of the interfacial interactions between the multicomponent fluid and kerogen. Such agreement demonstrates the reliability of the method and molecular models for modeling the complex interfacial interaction system. The results present a thermodynamic understanding and molecular details of the temperature effect on the oil interactions with kerogen, providing valuable insight into strategies for unconventional oil recovery.